The psychometric validation of the principal practices questionnaire based on item response theory / Corinne Jacqueline Perera, Bambang Sumintono, Jiang Na - Perera, C. J.; Sumintono, B.; Jiang, N. (Institute of Educational Leadership, Faculty of Education, Universiti Malaya, 2018)
This paper examines the psychometric properties of the Principal Practices Questionnaire (PPQ) for use in school leadership research. The PPQ has been developed as a diagnostic instrument to measure the various dimensions of transformational leadership based on the Rasch Measurement Model. With the growing awareness and importance given to psychometrics, particularly on interval measurement, this paper discusses the development of the PPQ and its psychometric properties based upon the framework of Item Response Theory (IRT). The PPQ was designed to determine the extent to which principals exhibit transformational leadership practices. The PPQ was validated using 290 secondary school teachers to elicit teacher's perceptions about their principals’ leadership practices. The sample comprised practising teachers from six high performing Malaysian public schools. In this study Rasch Model was used to determine the validity of the 30 questionnaire items based on the estimates of item difficulty and psychometrics attribute criteria. The results of this study showed that the PPQ may be supported by evidence as a valid research instrument because of its psychometric properties and internal consistencies. Having shown evidence of high reliability and statistical validity, the PPQ may therefore be used